Patients’, Carers’, and the Public’s Perspectives on Electroconvulsive Therapy - Griffiths, Chris; O’Neill-Kerr, Alex (Frontiers in Psychiatry, 2019)
Aims and Method To present patients', carers' and the public's perspectives on electroconvulsive therapy (ECT) through a narrative review of the literature. Results People’s perspectives on ECT are often negative due to media and internet portrayal. Perspectives are influenced by risks, short term side-effects and the most commonly reported longer term side-effect: memory loss. However, many patients do not report memory loss. Most people who experience ECT and their carers report a positive perspective. In the future people’s perspectives may become more positive with higher service delivery standards and a more balanced, well informed view of modern ECT presented by the media. However, ECT has risks and side effects, and negative and critical perspectives on the use and effects of ECT will persist. Clinical Implications Perspectives on ECT are important because of the impact on stigma, patient treatment choice, patient consent, provision of and referral for ECT.